2010
DOI: 10.3802/jgo.2010.21.2.102
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of levonorgestrel releasing intrauterine system in the treatment of endometrial hyperplasia in Korean women

Abstract: Objective: Levonorgestrel releasing intrauterine system (LNG-IUS) has been shown to treat patients with non-atypical & atypical endometrial hyperplasia (EH) successfully in many western studies. Our purpose was to examine the effectiveness of LNG-IUS in the treatment of Korean women with EH. Methods: We conducted a prospective observational study of 12 women diagnosed with EH and treated with LNG-IUS insertion between February 2007 and August 2009 at the Department of Gynecology of Gangnam CHA Hospital, CHA Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 15 publications
2
14
0
Order By: Relevance
“…This success rate matches with 66% regression rate within 3 months of Mirena application reported by others with a mean duration of 4.5 months [24]. Different regression times were reported in other studies as follows; range, 4 to 12 months (median, 6 months) [17]; range, 7 to 11.7 months (mean, 9.4 months) [23].…”
Section: Discussionsupporting
confidence: 87%
“…This success rate matches with 66% regression rate within 3 months of Mirena application reported by others with a mean duration of 4.5 months [24]. Different regression times were reported in other studies as follows; range, 4 to 12 months (median, 6 months) [17]; range, 7 to 11.7 months (mean, 9.4 months) [23].…”
Section: Discussionsupporting
confidence: 87%
“…The authors also reported that the LNG-IUS regression time ranged from 3 to 12 months (median, 3 months), a significant proportion of the patients (67.8%) having achieved regression by the 3rd month. This success rate accords with data reported by Lee et al[8] for a prospective observational study of 12 Korean women diagnosed with EH and treated with LNG-IUS. In that study, complete regression of EH was achieved in all cases (100%, 12/12), most of the patients (66%, 8/12) having attained it within three months.…”
supporting
confidence: 92%
“…The authors note that a recent trial reported almost equal EH-diagnostic success rates between Pipelle biopsy and dilatation & curettage (D&C) [9]; however, these results were obtained for cases where the LNG-IUS was not in the uterus and where there were no progestin effects on the endometrium. According to the reported literature, in cases of EH treatment using LNG-IUS, the endometrial response has been evaluated by endometrial aspiration biopsy while the LNG-IUS is in the uterus or by D&C after LNG-IUS removal [2-6,8]. Nevertheless, there has been no report comparing the accuracy of these methods.…”
mentioning
confidence: 99%
“…Qi et al (2008) reported that two infertile patients presented with complex atypical EH became pregnant following conservative treatment with LNG-IUS insertion, and histological morphology of endometrial samples after 6 months' exposure to LNG-IUS showed secretory or atrophic glands with decidualized stroma. Lee et al (2010) reported that complete regression of simple EH was achieved, after insertion of LNG-IUS in all cases with the significant proportion achieving it within 3 months and all cases had regression within 9 months, and in the case of complex atypical hyperplasia, the regression was attained at the 9th month after insertion of LNG-IUS and as long as LNG-IUS was maintained, the EH did not recur.…”
Section: Discussionmentioning
confidence: 99%